2011
DOI: 10.1596/978-0-8213-8669-9
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Mobile Money against Financial Crimes

Abstract: All rights reserved 1 2 3 4 14 13 12 11 This volume is a product of the staff of the International Bank for Reconstruction and Development / The World Bank. The findings, interpretations, and conclusions expressed in this volume do not necessarily reflect the views of the Executive Directors of The World Bank or the governments they represent. The World Bank does not guarantee the accuracy of the data included in this work. The boundaries, colors, denominations, and other information shown on any map in this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 2 publications
0
44
0
Order By: Relevance
“…Results indicated that 21.3% adults possess bank accounts and that micro-crediting remains limited. Chatain et al (2011) pointed that initiatives for financial inclusion, including mobile banking developments, in some countries are hampered by regulatory concerns that comply with proposed new regulatory models that include international financial integrity standards Dittus and Klein (2011) addressed other factors include religious or cultural reasons, or a limited trust for formal financial institutions, such as those who experienced bank failure or those who fear to become victims of fraud. Ellison et al (2010) pointed that customers who have access to formal financial services may withdraw from these institutions.…”
Section: Business and Economic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicated that 21.3% adults possess bank accounts and that micro-crediting remains limited. Chatain et al (2011) pointed that initiatives for financial inclusion, including mobile banking developments, in some countries are hampered by regulatory concerns that comply with proposed new regulatory models that include international financial integrity standards Dittus and Klein (2011) addressed other factors include religious or cultural reasons, or a limited trust for formal financial institutions, such as those who experienced bank failure or those who fear to become victims of fraud. Ellison et al (2010) pointed that customers who have access to formal financial services may withdraw from these institutions.…”
Section: Business and Economic Researchmentioning
confidence: 99%
“…In general, mobile banking models depend on a wide range of nontraditional agents, such as retailers, in providing cash-in and cash-out functions. Chatain et al (2008) found that the reach of service providers is extended while low service costs are maintained.…”
Section: Introductionmentioning
confidence: 99%
“…A study done by Chatain et al (2011) about financial crimes on mobile money aimed at contributing and providing guidance on policy, regulatory and the supervisory on anti-money laundering and combating financial terrorism (AML/CFT) of mobile money. In the documentary review and the survey done globally it was revealed that there is a substantial supportive opportunity, but the abuse can risk mobile money to support financial inclusion.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Mobile banking services, generally referred to as mobile money, are rendered via the mobile phones of clients (Chatain et al 2011). This form of service, especially to enable existing clients of banks to communicate with their bank and make balance enquiries or even payments, has been available in many developed countries for some time.…”
Section: Technology Increasing the Numbers Of Clients And Amount Of Datamentioning
confidence: 99%
“…A World Bank analysis (Chatain et al 2008(Chatain et al , 2011 identified the key risks as anonymity, elusiveness, rapidity and poor oversight. Anonymity and elusiveness are closely-linked to non face-to-face-account opening processes combined with the lack of public sources of information that could verify the identity of users in many developing countries.…”
Section: Mobile Money and Amlmentioning
confidence: 99%